COMPARATIVE ANALYSIS OF WORK-LIFE BALANCE AND EMPLOYEE PERFORMANCE INITIATIVES OF THE MONETARY AUTHORITY OF SINGAPORE (MAS) AND THE FINANCIAL SERVICES AUTHORITY OF INDONESIA (OJK) - Arquisola, Maria Jacinta; Irsan, Elisabeth Widyanty (President University, 2024)
This research examines the effectiveness of work-life balance (WLB) programs on employee performance at the Monetary Authority of Singapore (MAS) and the Financial Services Authority of Indonesia (OJK). The research investigates the approach of these two Southeast Asian financial regulators towards work-life balance (WLB) rules through the use of literature review, case analysis, and comparative framework evaluation. The data is obtained primarily from publicly accessible sources including organizational websites, publications, and prior research. The research focuses on the implementation of work-life balance (WLB) programs and the difficulties in sustaining work-life balance in the financial regulatory industry. This research offers insights into work-life balance (WLB) initiatives in the area by comparing the practices of MAS and Financial Services Authority Indonesia (OJK). It takes into organizational, and regulatory issues. This study provides insights into the most effective methods for achieving work-life balance (WLB) in financial regulatory organizations. This information has the potential to influence policy decisions related to effective human resource management practices through alternative working arrangements, not just in Southeast Asia but also in other regions.